La ludopatía y los docentes en la Universidad de San Buenaventura, seccional de Medellín, Colombia 2010 (2010)
This current study consists of a description of the use of games of chance and videogames by the students, instructors and employees at Saint Bonaventure University, Medellin branch and their relations with the medical and psychological dimensions in which the following variables were involved: difficulties for concentration, frame of mind, physical discomfort, the preference of games to sports, as well as the relaxed atmosphere produced by the game; in this second stage, the results given deal with university instructors. Federico Burgos Acevedo, Head of Roger Bacon Research Center, is responsible for the Epi-Info methodological assistantship. This study is endorsed by the Interdisciplinary Group of Psychosocial Studies in Addictions –GIEPSA – which is coordinated by Víctor Hugo Cano B, and Jorge Arturo Pérez P., being the main researcher, who belongs to the Research and Attention Center to the Drug Addict – CIAF –, which is directed by Francisco Javier Arias Zapata.